Augmentation cystoplasty in neurogenic bladder - Çetinel, Bülent (Investig Clin Urol, 2016)
The aim of this review is to update the indications, contraindications, technique, complications, and the tissue engineering approaches of augmentation cystoplasty (AC) in patients with neurogenic bladder. PubMed/MEDLINE was searched for the keywords "augmentation cystoplasty," "neurogenic bladder," and "bladder augmentation." Additional relevant literature was determined by examining the reference lists of articles identified through the search. The update review of of the indications, contraindications, technique, outcome, complications, and tissue engineering approaches of AC in patients with neurogenic bladder is presented. Although some important progress has been made in tissue engineering AC, conventional AC still has an important role in the surgical treatment of refractory neurogenic lower urinary tract dysfunction.